Force Majeure During COVID-19 Outbreaks: Case of the Cancellation and Termination of Government Construction Contracts - Muskibah Muskibah; Yetniwati Yetniwati; Sasmiar Sasmiar; Amarru Muftie Holish (Journal of Indonesian Legal Studies, 2023)
Force majeure is a contractual clause commonly found in government construction work contracts, defining the circumstances that qualify as absolute or relative force majeure. This research aims to address two key questions: First, can the force majeure clause be invoked to justify the cancellation and termination of construction work contracts amidst the Covid-19 pandemic? Second, what is the method of accountability for risks associated with construction work contracts in light of the pandemic? Employing normative juridical research methods, this study concludes that the Covid-19 pandemic alone cannot serve as an automatic basis for contract cancellation or nullification under the force majeure clause. The service user, typically the government, may demand the successful completion of the project from the providers. However, the pandemic qualifies as a relative force majeure, shifting the liability for risk during contract implementation to the provider, subject to court decisions. Thus, legal events qualifying as force majeure during the Covid-19 outbreak will be determined by court decisions.